Performance, Nutrient Utilization and Organ Characteristics of Broilers Fed Cassava Leaf Meal (Manihot esculenta Crantz) - Iheukwumere, F.C.; Ndubuisi, E.C.; Mazi, E.A.; Onyekwere, M.U. (Pakistan Journal of Nutrition, 2007)
A 35-day feeding trial involving 120, 5-week old Anak broilers was carried out in a completely randomized design to evaluate the performance, nutrient utilization and organ characteristics of broilers fed cassava leaf meal at dietary levels of 0, 5, 10 and 15% respectively. Feed intake, body weight gain, feed conversion ratio and organ weight of birds on the control (0%) and (5%) leaf meals were significantly superior (p